The Active Outward Orientation of the Organisation - George Angelopulo (Communicare)
A central problem of organisations is the uncertainty of their environmental transactions in the attainment of desired responses. The degree to which the uncertainty is reduced, is often associated with the organisation's offectiveness. This study examines and Identifies an appropriate theoretical framework within which to proceed with an Investigation into organisational effectiveness. The systems approach, although of limited ontological value, of. fers a valuable cluster of strategies for Inquiry, within which Heldema's partial. dy systems-derived view is discussed. According to this view, perceptions of real systems can be described along spatial and temporal dimensions: as ahistorical, Inward-looking and struc tural; or as historical, outward-looking and changing. From this, the active out. ward orlented perceptual paradigm is developed, and It Is suggested that the existence of the active outward oriented basic assumption is a necessary condition of the organisation's potential effectiveness, and that the process by which it is instituted and maintained is communication.